Assessment of Copper and Zinc Concentrations in Anadara granosa - Idris Nor Shahirul Umirah; Jamil Sarafiza; Zakaria Nur Najwa; Tatazi Muhammad Syamil Taufiq; Abdul Halim Nurul Syazana; Muhamad Nor Amal Najihah; Zulkifli Zarith Sofia (BIO Web of Conferences, 2023)
Due to economic growth and increased human activities, large amounts of metal pollutants have been discharged into the aquatic environment. Anadara granosa, which is a filter feeder cockle species, can act as an indicator to evaluate the presence of metal elements. It is a prominent cockle species and an important protein source in Southeast Asia. Thus, this study aims to evaluate the distributions of metal elements in commercialised Anadara granosa sampled from Jeli wet market, and to assess the safety of consumption using Target Hazard Quotients (THQ). The concentrations of Cu, and Zn in those samples were determined using the acid digestion method, which has been verified with standard reference material. Based on the findings, metal concentrations in Anadara granosa followed the order of; Zn > Cu. The differences in metal accumulation observed in Anadara granosa were probably due to the differences in their environmental conditions. Results from preliminary risk assessments suggest that the risks posed by metals via consumption of Anadara granosa for Cu and Zn were within the tolerable region. The Hazard Quotient (HQ) of, Cu and Zn was < 1, indicating no potential human health risk. However, it is advisable to limit the intake of Anadara granosa to reduce the risk of potential health effects.